Effects of Fiscal Rules - 85 Years' Experience in Switzerland - Heiko T. Burret; Lars P. Feld (Center for Economic Studies and ifo Institute (CESifo), 2016)
The paper investigates the fiscal effects of Swiss cantonal debt brakes by taking explicitly into account the rules' coverage. An in-depth analysis provides unique evidence that suggests the following: First, fiscal rules at the cantonal level have a negative effect on public deficits, which is stronger the better the analyzed budget position corresponds with the variable targeted by the rules. Second, cantonal debt brakes are rather not associated with substantial evasive measures. Third, cantonal fiscal rules tend to mitigate political budget cycles and shock-related deficits.
Keywords: H72; H74; H77; D72; K39; 330; Switzerland; fiscal rule; debt brake; budget cycle; election; fiscal shock